Dietary pattern of food and beverage consumption patterns in patients oral squamous cell carcinoma: Study cross-sectional - Izzul Haq, Muhammad Fadhlan; Setiawan, Asty Samiaty; Anggraini, Jamas Ari (Padjadjaran Journal of Dental Researchers and Students, 2025)
ABSTRACTIntroduction: Oral squamous cell carcinoma (OSCC) is one of the most common cancers in the world. Changes in food consumption patterns and lifestyle can increase the risk of cancer. Studies on the description of food and beverage consumption patterns in malignancies of the oral cavity in Indonesia are still inadequate. This study aims to determine the description of food and beverage consumption patterns in patients with oral malignancies. Methods: The type of research used was descriptive observational research with a cross-sectional approach. The population in this study were patients with OSCC in the Oral Surgery Poly of Hasan Sadikin Hospital, Bandung City during the period September to November 2024. The sampling technique used a non-probability sampling technique, namely accidental sampling. Data collection was carried out using the Food Frequency Questionnaire (FFQ). Results: The results showed that the most frequently consumed food and beverages per day by OSCC patients based on food groups were rice, eggs, meatballs, salted fish, milk, cucumber, banana, flavoring “M” and coffee. Conclusions: Dietary pattern of food and beverage consumption patterns in OSCC patients, the majority have a high level of food consumption of carcinogenic foods. Meanwhile, the level of consumption of foods with chemopreventive properties is relatively low.KEY WORDS: Food and beverage patterns, oral squamous cell carcinoma, oral malignancies, cancer risk, FFQPola konsumsi makanan dan minuman pada penderita oral squamous cell carcinoma: Studi cross-sectionalABSTRAKPendahuluan: Oral squamous cell carcinoma (OSCC) merupakan salah satu kanker yang paling umum terjadi di dunia. Perubahan pola konsumsi makanan dan gaya hidup dapat meningkatkan risiko kanker. Studi mengenai gambaran pola konsumsi makanan dan minuman pada penyakit keganasan pada rongga mulut di Indonesia masih belum memadai. Penelitian ini bertujuan untuk mengetahui gambaran pola konsumsi makanan dan minuman pada penderita keganasan rongga mulut. Metode: Jenis penelitian yang digunakan adalah penelitian deskriptif observasional dengan pendekatan cross sectional. Populasi dalam penelitian ini adalah pasien penderita OSCC di Poli Bedah Mulut Rumah Sakit Hasan Sadikin Kota Bandung selama periode September sampai dengan November 2024. Teknik pengambilan sampel menggunakan teknik non probability sampling yaitu accidental sampling. Pengambilan data dilakukan menggunakan Food Frequency Questionnaire (FFQ) Hasil: Bahan makanan dan minuman perharinya yang paling sering dikonsumsi oleh penderita OSCC berdasarkan kelompok makanannya adalah nasi, telur, bakso, ikan asin, susu, mentimun, jeruk, pisang, penyedap rasa “M” serta kopi non instan. Simpulan: Pola konsumsi makanan dan minuman pada penderita OSCC memiliki kecenderungan mengkonsumsi makanan atau minuman yang bersifat karsinogenik lebih banyak dibandingkan makanan atau minuman yang memiliki khasiat kemopreventif.KATA KUNCI: Pola makanan dan minuman, oral squamous cell carcinoma, keganasan rongga mulut, risiko kanker, FFQ